Gestation‐specific changes in maternal thyroglobulin during pregnancy and lactation in an iodine‐sufficient region in China: a longitudinal study - Zhang, Xiaowen; Li, Chenyan; Mao, Jinyuan; Wang, Weiwei; Xie, Xiaochen; Peng, Shiqiao; Wang, Zhaojun; Han, Cheng; Zhang, Xiaomei; Wang, Danyang; Fan, Chenling; Shan, Zhongyan; et al. (Clinical endocrinology (Oxford), 2017)
Summary Objectives To describe the changes in thyroglobulin (Tg) based upon gestational and postpartum concentrations in healthy pregnant women from an iodine‐sufficient region in China, and to evaluate the use of Tg as a biomarker for iodine‐sufficient pregnant women. Design A longitudinal study of Tg change in normal pregnant women from an iodine‐sufficient region. Patients and measurements Blood and urine samples were obtained from 133 pregnant women. Urinary iodine concentration (UIC) was measured using an ammonium persulfate method. Serum iodine concentration was required by inductively coupled plasma mass spectrometry (ICP‐MS). Serum thyroid‐stimulating hormone (TSH), free thyroxine (FT4), free triiodothyronine (FT3), total thyroxine (TT4), total triiodothyronine (TT3), antithyroid peroxidase antibody (TPOAb), antithyroglobulin antibody (TgAb) and Tg were measured using an electrochemiluminescence immunoassay. Results Thyroglobulin concentrations were higher in early pregnancy (pregnancy at 8 weeks vs nonpregnancy: 11·42 ng/ml vs 8·8 ng/ml, P < 0·01) and maintained a stable level, and then increased greatly at the 36th week. After delivery, Tg decreased to nonpregnant levels. During pregnancy, maternal Tg was not correlated with thyroid function, UIC or urine iodine–creatinine ratio (UI/Cr). Cord blood Tg was much higher compared to maternal Tg levels at the 36w (57·34 vs 14·86 ng/ml, P < 0·001) and correlated positively with cord FT4 (r = 0·256, P < 0·05), cord TT4 (r = 0·263, P < 0·05) and maternal UI/Cr at 36w (r = −0·214, P < 0·05). Conclusions Our work demonstrates that Tg is elevated during pregnancy, and the effect of pregnancy should be taken into consideration when Tg is used as a biomarker for the iodine status. Cord blood Tg is much higher than maternal Tg levels at the 36w and is correlated with maternal iodine status.